PERANAN WORK-LIFE BALANCE DALAM MENINGKATKAN KINERJA GURU DI SDN JERUK 1 SURABAYA - Fatimah Al Alawiyah; Feby Nabila Inova, Farhana Laily Nur Hidayah, Syunu Trihantoyo, Nuphanudin (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine the role of work-life balance in improving teacher performance at SDN Jeruk 1 Surabaya. This research uses qualitative methods with in-depth interviews with different teachers at SDN Jeruk 1 Surabaya. Research shows that work-life balance has a positive effect on teacher motivation, job satisfaction and creativity. Teachers who are able to maintain a balance between work and home life tend to be more productive, have positive energy, and make maximum contributions to the learning process. In addition, work-life balance can also help reduce stress and fatigue, as well as improve teachers' mental and physical health. The importance of school policies and institutional support in creating a work environment that supports work-life balance is also an important finding of this study. Supports such as changes to workload policies, time flexibility, and time management can help teachers achieve a better balance. This research concludes that work-life balance plays an important role in improving teacher performance at SDN Jeruk 1 Surabaya. Therefore, deeper consideration of this aspect can have a positive impact not only on individual teachers but also on the quality of education as a whole.